Sexual cannibalism in the spider Alpaida veniliae (Keyserling 1865) (Araneae: Araneidae) - Benamú, Marco A. (2015)
Postmating cannibalism where a female attacks, kills and consumes a male after a sexual encounter is frequently influenced by certain male morphological and behavioral characteristics. We conducted behavioral assays in the laboratory to test the predictions that male Alpaida veniliae (Keyserling 1865) with larger absolute and relative size in relation to their mate and those having longer courtship and copulation duration would have lower probability of being cannibalized by females after a sexual encounter. We performed a set of mating trials exposing males of different sizes to virgin females. We observed copulation in 88.8% of mating trails; its duration was very brief compared to courtship. Only a few attempts (16.7%) of recopulations with the same female were recorded, and in all these cases the first copulation was significantly shorter than the mean copulation duration of those who had only one copulation. The percentage of postcopulatory cannibalism was 47.6%. There was no correlation between the relative and absolute male size and duration of courtship and copulation. Postcopulatory cannibalism was independent of courtship and mating durations but was affected by absolute and relative male size. Smaller males were more frequently cannibalized than large ones. However, it remains unclear whether sexual cannibalism in A. veniliae may be explained by female mate choice or whether smaller males are less able to escape or defend themselves. More studies are needed to understand the underlying factors of postcopulatory cannibalism of A. veniliae, as well as to elucidate their possible ecological and evolutionary implications.